SISTEM MAWAH DAN KESEJAHTERAAN PETANI PADI DI KECAMATAN SEULIMUM KABUPATEN ACEH BESAR - Akram Dermawan; Nur Aidar; Talbani Farlian; Amri Amri; Nanda Rahmi (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2022)
AbstractThis research aims to determine the practice of mawah in Seulimum subdistrict , Aceh Besar district and its relation to the welfare level of rice farmer families in Seulimum. The variables in this research include land area, income, expenditure, and Farmer’s Exchange Rate  (NTP). The method used in this research is descriptive analysis method. The participants of this research are fifty-four farmers in Seulimum, Aceh Besar district. The findings indicate that the average area of land rented by farmers ranged from one to two hectares, with a price of four thousand five hundred rupiahs per kilogram. The average income of rice farmers in Seulimum subdistrict is around twenty-two million twenty thousand three hundred and seventy rupiahs in one growing season. The average expenditure of farmers in one growing season is nine million eight hundred eighty-eight thousand three hundred rupiahs. The NTP in the village of Seulimum subdistrict is more than a hundred showed that the farmer has a surplus where the farmer's income is greater than his expenditure. From the result of this research, it can be concluded that the welfare level of farmers who practice mawah in Seulimum subdistrict, Aceh Besar District is quite good.  Keywords:  Rice Farmer, System Mawah, Welfare,Seulimum Distric